Dipeptidyl peptidase-4 inhibition of Peronema canescens Jack leaves and stems: Bioassay-guided fractionation, compound profiling by LC-MS/MS, and interaction mechanism - Berna Elya, Roshamur Cahyan Forestrania, Najihah Mohd Hashim, Nita Triadisti (Journal of Applied Pharmaceutical Science, 2024)
Sungkai (Peronema canescens Jack) has been used for generations as a traditional antidiabetic drug for the Borneo people, but scientific data as a dipeptidyl peptidase-4 (DPP-4) inhibitor has never been reported. This study aims to obtain the most active chromatographic fraction as a DPP-4 inhibitor and the profile of the compounds contained. Bioassay-guided fractionation was used in this study and bioassays using spectrofluorometric principles. Compound profiling is carried out using ultra-performance liquid chromatography coupled with electrospray ionization/quadrupole-time-of-flight mass spectrometry (UPLC-ESI-QToF-MS/MS), and molecular docking is used to investigate interactions between compounds and DPP-4. The study found that the most effective extracts were ethyl acetate and methanol extracts from the leaves, which showed inhibitory percentages of 70.0% ± 0.7233% and 59.69% ± 1.9394%, respectively, at a concentration of 100 μg/ml. The fractionation produces the most active fraction, the second fraction from P. canescens methanol extract (FPSM2 fraction), with a percent inhibition of 88.28% ± 2.1204%. The compounds contained in FPSM2 were identified through UPLC-ESI-QToF-MS/MS, including pectolinarigenin, glycitein, formononetin, latifoline, 3-oxo-alpha-ionol, moracin M, and loliolide. Assay results showed that P. canescens has been shown to have inhibitory activity against DPP-4, suggesting that this plant has excellent potential to be developed as a DPP-4 inhibitor.
Keywords: Peronema canescens Jack, dipeptidyl peptidase-4 (DPP-4), bioassay-guided fractionation, UPLC-ESI-QToF-MS/MS, compound profiling